Effectiveness of Deep Breath Relaxation Techniques and Music Therapy on Reducing Anxiety Level among Preoperative Patients - Mohamad Malikul Mulki Mulki; Ta’adi Ta’adi; Lanny Sunarjo (Alta Dharma Publisher, 2021)
Operation is a form of action or surgery that is frightening for everyone. Surgery can threaten the integrity of a person's body and soul so that it can cause a physiological response in preoperative patients, namely anxiety. Reducing anxiety before surgery is very important for patients, one of them with complementary therapy. Alternative treatments with complementary therapies, namely deep breath relaxation techniques and music therapy that can overcome preoperative patient anxiety levels. This study aims to analyze the effectiveness of deep breath relaxation techniques and music therapy on reducing the anxiety level of preoperative patients. This study quasi experimental used a noneqiuvalent pre-test and post-test approach control group design involving 42 preoperative patients. Selected through technique non-probability sampling with method consecutive sampling divided into 2 groups, namely 21 respondents in the intervention group who were given deep breath relaxation technique and music therapy, while 21 respondents in the control group were only given music therapy without deep breathing relaxation techniques. Measurement of anxiety level was carried out twice before and after treatment, then the data were analyzed using Paired t test and Independent t test. Independent t test showed significant difference p value of 0.000 (<0.05) that the intervention group better well in lowering anxiety levels compared with the control group. In conclusion, deep breath relaxation techniques and music therapy effectively lowered anxiety level in preoperative patients.